WORKING CONDITIONS IN THE EUROPEAN UNION MEMBER STATES (Innovation in Woodworking Industry and Engineering design, 2026)
The European Union (EU) policy, concerning employment and social activities, recog-nizes competitiveness and sustainability as essential goals for the EU to be achieved through building an economically dynamic labour market. To achieve these objectives, the EU should modernise working life, creating ‘more and better jobs’ as specified in the Lisbon Strategy, and deliver ‘smart, sustainable and inclusive growth’ according to the words of the Europe 2020 strategy. Ensuring quality of work and employment and healthy and safe working condi-tions are core elements in achieving these objectives.A research on the dynamics of working conditions in EU member states has been carried out in the present article on the basis of the results from the fifth European Working Condi-tions Survey.